Dyslipidemia, Diabetes Mellitus, Rheumatoid Arthritis: Association Study Between them in a Group of Individuals in Shijak Population (International Journal of Scientific Research and Management (IJSRM), 2021)
The aim of the study was to evaluate the association between Dyslipidemia, Diabetes Mellitus and Rheumatoid Arthritis in a population of 289 individuals ( 154 female and 135 male ), for the year 2020 ( January – December ) and the year 2021 ( January – July ), where 85.8 % are patients with Diabetes Mellitus ( DM ) , 9.7 % are patients with Dyslipidemia and 4.5 % are patients with Rheumatoid Arthritis ( RA ). Diseases are analyzed separately from each – other calculating the correlation based on the values of the main analytical components for each disease. From this study it was determined that the number of individuals with DM and Dyslipidemia is the highest in the age group VII ( 65 years and above ). The highest average value of glycemia is in the age group V ( 45- 54 years old ), with value 195 mg/ dl for the female gender and 218.4 mg/ dl for the male gender. In individuals with DM has significant correlation values between glycemic – triglycerides with Pearson correlation Value 0.157. Individuals with Diabetes have a high tendency to be affected by Dyslipidemia. In patients with Dyslipidemia significant correlation value are between Cholesterol- Glycemi with Pearson correlation value 0. 555. Individuals with Dyslipidemia have a high tendency to be affected by DM. In patients with RA the largest number of individuals is in the age group V and VI. Females are in greater number than males. The highest erythrocyte sedimentation rates are in the age group VII, with average value 21.5 mg/ dl. Higher correlation value is between erythrosediment – LDL- Ch with value 0.93. Individuals with RA have a high tendency to be affected by Dyslipidemia. The knowledge gained from this study are important to determine the correct diagnosis for primary and concomitant diseases recognizing risk factors. Prevention of diseases at an early stage and prevention of comorbidities to avoid deteriorating health.